Studi Perencanaan Sistem Off-Site Pengolahan Air Limbah Black Water Di Desa Bener Baru Kabupaten Gayo Lues Provinsi Aceh - Putra, Alpinsyah; Rahma, Pamela Dinar; Khaerudin, Dian Noorvy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Planning an off-site wastewater treatment system is one of the meaningful aspects in supporting the infrastructure of an area or region. This study aims to determine the population for the next 10 years, domestic water demand, non-domestic water demand, clean water demand and black water wastewater discharge and gray water wastewater discharge and planning wastewater treatment plants (WWTP). This research collects data in the form of primary data, secondary data and planning of wastewater treatment plants (WWTP) for the next 10 years. The calculation of the population for the next 10 years, namely in 2032, is 745 people and domestic water demand (Qd) = 0.518 liters / second and non-domestic water demand (Qn) = 0.026 liters / second and clean water demand = 0.625 liters / second and black water waste discharge (Q_BW) = 0.100 liters / second and gray water waste discharge (Q_GW) = 0.500 liters / second.